2018
DOI: 10.1093/pubmed/fdy006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends and risk factors for tobacco, alcohol and drug use among adolescents in Scotland, 2002–13

Abstract: Further effort is required to tackle heavy alcohol and heavy illicit drug use amongst adolescents in Scotland. Prevention strategies should be informed by the risk profiles of substance misusers and evidence around the clinical and cost-effectiveness of preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…Our study also showed that the wealthiest adolescents presented the highest prevalence of drug experimentation. The literature, on the other hand, shows that drug use is usually higher among adolescents from lower socioeconomic positions 46–48 . In agreement with our results, lower HPV vaccination prevalence has been observed among socioeconomically disadvantaged girls 49 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study also showed that the wealthiest adolescents presented the highest prevalence of drug experimentation. The literature, on the other hand, shows that drug use is usually higher among adolescents from lower socioeconomic positions 46–48 . In agreement with our results, lower HPV vaccination prevalence has been observed among socioeconomically disadvantaged girls 49 .…”
Section: Discussionsupporting
confidence: 92%
“…The literature, on the other hand, shows that drug use is usually higher among adolescents from lower socioeconomic positions. [46][47][48] In agreement with our results, lower HPV vaccination prevalence has been observed among socioeconomically disadvantaged girls. 49 This association could be explained by lower knowledge about HPV infection and the importance of the vaccine for its prevention in this population.…”
Section: Discussionsupporting
confidence: 92%
“…The transition from adolescence to early adulthood is an important, and yet often overlooked period, with significant implications for physical and mental health across the life course 1,4,5 . Poor physical health in adolescence, such as being overweight or obese, and risk behaviours such as substance misuse 5,6 , are linked to increased risk of chronic disease in adulthood 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The main existing public policies to prevent substance abuse, such as Proerd, educational booklets provided in schools and Guide-AD, predominantly cover the young population, with no easy access to this information for older age groups 34. Regarding the reception, monitoring and rehabilitation of this population in the public sphere, there are CAPS-AD (Psychosocial Care Center for Alcohol and Drugs), coordinated by the Health Department 35. Although they exist, they do not cover the entire population in need, so there are other charitable and voluntary organizations that also work in this sector, such as AA (Alcoholics Anonymous) and NA (Narcotics Anonymous) 36 • family relationships 17,[19][20][21][22]37,45 • Healthy family relationships 19.20 • School dropout or low academic performance 17,19,37 • Involvement in social and cultural activities 37 • Violent youth (recurrent involvement in fights) 19,20,37 • Religious Activities 21.37 • Beginning of sexual intercourse in adolescence (early) 19 • Encouraging educational activities 17.19 • Intolerance to frustration 21.37 • School environment with strict rules 19.37 • Parental permission to use drugs 22,37 • Parental monitoring 17 • Low socioeconomic power 23.37 • Anti-drug education programs 22,21,23 • Misconduct 37 • Prohibition on the sale of alcoholic beverages and tobacco to minors 21 • Parents' marital status (widowed/separated/divorced) 19 • Parental permission to use drugs 22,37 18 to 61…”
Section: Resultsmentioning
confidence: 99%